230k views
3 votes
24x - 22 = -4 (1 - 6x)

User Hop
by
4.7k points

2 Answers

4 votes

Answer:

ffdfssss

Explanation:

fdfdfdfd

User Brezotom
by
5.0k points
1 vote

Answer:

x is invalid.

Explanation:

Note the equal sign, what you do to one side, you do to the other. Remember to follow PEMDAS.

PEMDAS is the order of operation, and =

Parenthesis

Exponents (& Roots)

Multiplication

Division

Addition

Subtraction

First, distribute -4 to all terms within the parenthesis:

-4(1 - 6x) = (-4 * 1) + (-4 * -6x) = -4 + 24x

24x - 22 = -4 + 24x

Isolate the variable, x. Subtract 24x from both sides:

24x (-24x) - 22 = -4 + 24x (-24x)

0 - 22 = -4 + 0

-22 ≠ -4, therefore, this question is invalid.

~

User Raphael Oliveira
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.